Chromatography-tandem MASS spectrometry (HPLC-MS/MS) for the detection of valproic acid and its metabolites in blood plasma - A. S. Malygin; N. S. Popov; M. A. Demidova; M. N. Kudrayshova (Эпилепсия и пароксизмальные состояния)
Aim: to adapt the HPLC-MS/MS technique to determining valproic acid and its metabolites in blood plasma for drug therapy monitoring.Materials and Methods: The chromatographic assay was run using an Agilent 1260 Infinity II chromatograph with a Phenomenex synergi Fusion analytical column 4 μm-C18 2×50 mm. The mobile phase consisted of 0.1% ammonium acetate in distilled water and 0.1% ammonium acetate in methanol (10:90 v/v, 0.5 ml/min). The multiple ions monitoring (MIM) mode was used for mass- spectrometric detection of valproic acid at m/z = 143.1, with the negative ion mode. The method  was found applicable over the range from 1 mcg/ml to 200 mcg/ml of valproic acid. For the mass  spectroscopy detection of valproic acid metabolites, the multiple reaction monitoring (MRM mode)  was used. MS identifications of 2-propyl-4-pentanoil-β-О-glucuronide; 2-propyl-4-pentenoic acid,  3-hydroxy-2- propylpentanoic acid, 4-hydroxy-2-propylpentanoic acid, 2-propylglutaric acid and 3- oxo-2-propylpentanoic acid in the negative ion mode were carried out at m/z 319.2→143.2; m/z  140.1→140.1; m/z 159.1→101; m/z 159.1→123.1; m/z 173→129.1 and m/z 157.05→11,  respectively. The method was sensitive over the range from 10 ng/ml to 500 ng/ml of the tested  compounds.Results: The developed technique allows for determining valproic acid and its metabolites in a single sample; thus, the preliminary stage of separate sample preparation can be omitted, which increases the informative value of the assay without increasing its cost.Conclusion: This innovative methodology for the quantification of valproic acid and its metabolites in the blood plasma is expected to facilitate the individual approach to the treatment of patients with epilepsy, thereby increasing the efficacy and safety of the pharmacotherapy.